Methodology of creation of cryptographic transformations on the basis of methods excluding redundancy - Barannik, Vladimir; Sidchenko, Sergey; Larin, Vladimir (Видавництво Львівської політехніки, 2010)
Substantiation of is spent that for increase of efficiency of processing and delivery of the video data with use information communication systems of real time it is required to carry out cryptographic enciphering simultaneously with the organisation of compact representation.
Keywords: enciphering; compression